SYNTHESIS AND ANTITUMOR-ACTIVITY OF POLYANION-PT-COMPLEXES CONTAINING ALICYCLIC AMINES AS LIGANDS - HAN, MJ; PARK, SJ; CHO, TJ; CHANG, JY; SOHN, YS; LEE, CO; CHOI, SU (TECHNOMIC PUBL CO INC, 1994)
Four polyanion-Pt(II)-complexes, PEE-cis-DACH-Pt, PEE-cis-(ACP)2-Pt, PCP-cis-DACH-Pt, and PCP-cis-(ACP)2-Pt, were synthesized by the reactions of polyanions such as poly[(2-ethoxytetrahydropyran-5,6-diyl)(1,2-dicarboxyethylene)](PEE) and poly[(3,4-dicarboxytetrahydropyran-2,6-diyl)-(1,2-dicarboxypropylene)](PCP) with cis-[Pt(amine)2)2](NO3)2, where the amine was 1,2-diaminocyclohexane (DACH) or aminocyclopropane (ACP). The biological activities of the complexes were measured in vitro against A-459 nonsmall cell lung, Sk-OV-3 ovarian, SK-Mel-2 melanoma, XF-498 CNS, and HCT-15 colon tumor cell lines. The increased life span was measured against L1210 leukemia and found to be 223% for PCP-cis-(ACP)2-Pt(II) at the dose of 25 mg/Kg.